2008
DOI: 10.1291/hypres.31.941
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Gene Expression Associated with Genetic Cardiac Hypertrophy in the Absence of Hypertension

Abstract: The hypertrophic heart rat (HHR) was derived from the spontaneously hypertensive rat of the Okamoto

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…A zebrafish model of Costello syndrome expressing oncogenic H-RASV12 also had thicker heart walls [Santoriello et al, 2009], but the observed defects in early heart morphogenesis cannot be directly compared to humans with Costello syndrome (most of whom have the p.G12S mutation). The mitogen-activated protein kinase (MAPK) cascades, p38, JNK, and ERK, have profound effects in the development of HCM and remodeling [Harris et al, 2004;Dwyer et al, 2008;Rohini et al, 2010;Streicher et al, 2010]. However, it is important to note that the myocardial phenotypic heterogeneity is striking.…”
Section: Genotype-phenotype Correlationmentioning
confidence: 99%
“…A zebrafish model of Costello syndrome expressing oncogenic H-RASV12 also had thicker heart walls [Santoriello et al, 2009], but the observed defects in early heart morphogenesis cannot be directly compared to humans with Costello syndrome (most of whom have the p.G12S mutation). The mitogen-activated protein kinase (MAPK) cascades, p38, JNK, and ERK, have profound effects in the development of HCM and remodeling [Harris et al, 2004;Dwyer et al, 2008;Rohini et al, 2010;Streicher et al, 2010]. However, it is important to note that the myocardial phenotypic heterogeneity is striking.…”
Section: Genotype-phenotype Correlationmentioning
confidence: 99%
“…In addition to genetic lesions, pathological stimuli, like biomechanical stress and neurohumoral factors, lead to a hypertrophic state of the heart (26)(27)(28). The altered stimulation of membrane receptors, such as RTKs, is a crucial initiating step leading to the final activation of MAPKs, which thereby induce the hypertrophic response (27,(29)(30)(31)(32)(33). By altering the levels and activities of cardiac transcription factors (for example, GATA binding protein 4 [GATA4], myocyte enhancer factor 2 [MEF2] and nuclear factor of activated T cells [NFAT]), the RAS/RAF/MEK/ MAPK pathway leads to reexpression of fetal cardiac genes (34).…”
Section: Pathophysiological Signaling: Experimental Relevance Of the mentioning
confidence: 99%
“…The model was successfully developed by cross breeding the spontaneously hypertensive rat (SHR) with the Fischer (F‐344) rat. A number of genes potentially associated with concentric cardiac hypertrophy were demonstrated to be altered in the HHR following microarray analysis (Dwyer et al., ). For instance, DnaJ homolog subfamily A member 3 ( DNAJA3 ) was overexpressed in young HHRs.…”
Section: Cardiac Hypertrophy: the Good And The Badmentioning
confidence: 99%
“…DNAJA3 encodes for Ras GTPase‐activating protein binding protein (RasGAP) which has a central role in hypertrophic signalling (Trentin et al., ). Similarly, guanine nucleotide binding protein gene ( GNG5 ), Rab12 – a Ras (rat sarcoma) oncogene family member – and mitogen activated protein kinase 1 ( MAPK1 ) were overexpressed, these genes are involved in the Ras/mitogen‐activated protein kinase (MAPK) signalling pathway that results in cardiac hypertrophy (Dwyer et al., ). Four important genes from the microarray data were validated via real‐time polymeric chain reaction (PCR) and suggested to be involved with cardiac hypertrophy (Dwyer et al., ).…”
Section: Cardiac Hypertrophy: the Good And The Badmentioning
confidence: 99%
See 1 more Smart Citation